A számítógép alapú tesztelés elfogadottsága pedagógusok és diákok körében - Molnár, Gyöngyvér; Magyar, Andrea (Magyar Pedagógia, 2015)
Assessment represents one of the most dynamically developing areas in education in the past decade and a half, within which technology-based data collection has played an increasing role. Most studies on the conversion from traditional paper-and-pencil (PP) to computer-based (CB) testing have focused on the effect of testing medium on achievement, but there is a lack of research on the acceptance of online testing among teachers and children. The aim of this study is to survey this area and specifically to ascertain: (1) the opinions of (1a) teachers and (1b) children on CB testing formed on the basis of their experience to date and (2) the degree of acceptance of the introduction of CB testing among particular school years with respect to (2a) systemwide and (2b) small-scale diagnostic testing. The sample for the research consisted of nearly 10,000 participants, of whom 1,322 were teachers and 8,614 were children in Years 5 to 12. The reliability index of the 75-item teacher questionnaire was α=0.95, while it was α=0.80 for the 45-item pupil questionnaire. The data collection took place in spring 2014 through the eDia online assessment system. The results showed that the computer did not pose a problem as a new medium for the majority of the children and that most of the age group in Years 5 to 12 possess all the IT skills and abilities required to complete a test, recognise tasks, enter responses and navigate between tasks. Those schoolchildren who had had relatively more experience, that is, those who had already participated in electronic testing more than once preferred the spread of and conversion to online testing compared to those who had not had similar experience. A total of three-quarters of the children would support the spread of CB assessment, independent of the weight of the test in question.These trends and the variables behind them were identical for teachers with experience; however, support for technology-based testing is even stronger among teachers. 90% of the teachers were clearly supportive with regard to this question; in fact, they stressed the need to introduce both small-scale and systemwide assessment. In the case of teachers, a link has also been observed such that teachers with relatively greater experience had a more positive opinion of electronic tests and the change in mediumthan those who had not seen a CB test.